DSS for best e-commerce selection using AHP-WASPAS and AHP-MOORA methods - Gede Surya Mahendra; I Wayan Widi Karsana; Anak Agung Istri Ita Paramitha (Unit Publikasi Ilmiah, P3M Politeknik Negeri Bali, 2021)
eIQ Consumer Pulse 2019 determines the 6 largest e-commerce in Indonesia, namely Blibli, Bukalapak, JD.id, Lazada Indonesia, Shopee and Tokopedia. This is due to an increase in e-commerce transactions. The COVID-19 pandemic, which emphasizes social distancing and physical distancing, has also played a role in increasing these transactions. Indonesia is also predicted to become the market leader in Southeast Asia due to this. On the other hand, each e-commerce customer has their preferences in choosing e-commerce to use in transactions. Various criteria make customers confused due to intense competition between e-commerce companies. DSS is a solution in choosing the right e-commerce for each customer's preferences. The AHP-WASPAS and AHP-MOORA methods can be used in calculations for determining favorite e-commerce in Indonesia. The CRISP-DM framework also helps in preparing the research flow well. 3 decision-makers are used to provide weighting criteria using AHP. The results of this study indicate that the Tokopedia alternative is the best e-commerce, with a preference value of 0.8964 for AHP-WASPAS and 0.4245 for AHP-MOORA. The second and third places are Bukalapak and Lazada, respectively. The weighting of the criteria by the decision-maker, the alternative normalization process and the calculation technique for the preference value have a significant impact on the ranking results.